Metabolic Control of Epilepsy: A Promising Therapeutic Target for Epilepsy - Fei, Yanqing; Shi, Ruting; Song, Zhi; Wu, Jinze (Frontiers in Neurology, 2020)
Epilepsy is a common neurological disease that is not always controlled, and the ketogenic diet shows good antiepileptic effects drug-resistant epilepsy or seizures caused by specific metabolic defects via regulating the metabolism. The brain is a vital organ with high metabolic demands, and epileptic foci tend to exhibit high metabolic characteristics. Accordingly, there has been growing interest in the relationship between brain metabolism and epilepsy in recent years. To date, several new antiepileptic therapies targeting metabolic pathways have been proposed (i.e., inhibiting glycolysis, targeting lactate dehydrogenase, and dietary therapy). Promising strategies to treat epilepsy via modulating the brain's metabolism could be expected, while a lack of thorough understanding of the role of brain metabolism in the control of epilepsy remains. Herein, this review aims to provide insight into the state of the art concerning the brain's metabolic patterns and their association with epilepsy. Regulation of neuronal excitation via metabolic pathways and antiepileptic therapies targeting metabolic pathways are emphasized, which could provide a better understanding of the role of metabolism in epilepsy and could reveal potential therapeutic targets.